GAMBARAN HISTOPATOLOGI BEBERAPA TIPE BRONCHOPNEUMONIA PADA PULMO BABI HASIL PEMOTONGAN DI RPH OEBA - Hermilinda Parera; Aven B Oematan; Victor Lenda (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2018)
The aim of this study was to determine the histopathologic changes of bronchopneumonia type in pigs of slaughtered pig from Oeba slaughterhouse associated with P. multocida infection. Samples of pulmo were found from pigs showing respiratoric symptoms, characterized as dyspnoea and presence of nasal exudates that are serous to mucopurulent, obtained from slaughtered pigs in RPH Oeba Kota Kupang. Samples showed pathognomonic lesions of gray hepatized than processed for histopathological studies. The result showed that varied macroscopic changes noted in pulmo samples from suspected infected pigs showed various types of lesions. Lessions observed then classified into two main lessions were acute and chronic. Acute lesions were characterized by edema and hyperemia which then confirmed with congestion and multifocal haemorrhages. Serous to seromucous exudates were observed intrabronchial and bronchioles. In chronic cases, the lesions showed cranioventral consolidation and gray hepatized with demarcated area beetwen consolidated and normal pulmonary area. Histologically, the types of bronchopneumonia categorized into bronchopneumonia suppurativa characterized by coagulative necrosis surrounded by cell infiltration and accumulation of fibrin intraalveolar. The fibrous connective tissue were also observed in the interstitaial space of alveolar around the necrotic area. Other samples showed non-suppurativa fibrinous bronchopneumonia with alveolar exudates dominated by mononuclear cells and accumulation of fibrin intra alveolar. Chronic bronchiolitis also seen with a mixture of mononuclear cells, neutrophils and macrophages that infiltrated into the lumen of the alveoli. A high number of goblet cells were observed in the bronchiolus epithelium, with the thickening of the fibrous tissue around the bronchioles. It can be concluded that there are two major types of lesions which are acute and chronic, with three types of bronchopnemonia namely bronchopneumonia suppurativa, non supuratival bronchopneumonia and chronic bronchiolitis.